Tugu Ngejaman: Penanda Kuasa dan Pengingat Waktu di Yogyakarta - Heronimus Heron (Retorik: Jurnal Ilmu Humaniora, 2022)
Tugu Ngejaman or Stadsklok is a monument to commemorate a century of the return of Java to the Dutch colonial rule in 1916. This story begins with the French conquest of the Netherlands in January 1795 which led to the conquest of Java in 1808-1811. But France finally lost the war against Russia in 1814, so the Netherlands negotiated with Britain over its colonies. The British and the Dutch managed to reach an agreement to cede Java to the Dutch, while the British took control of Malacca in 1816. In this paper, I trace the history of the establishment of the Ngejaman monument, the meaning of the Ngejaman monument for the Dutch population in Yogyakarta, and the reasons for maintaining the Ngejaman monument today. I use Walter Benjamin's perspective on aura to explore the relationship between monuments and history and the technological revolution. The data in this paper comes from archival documents and existing scholarly literature, interviews, as well as field observations that elucidate the Ngejaman monument and the activities of the surrounding community. This study finds that the construction of the Ngejaman monument was related to the markers of Dutch colonial power in Yogyakarta and the "revolution of time" in the modern society. However, the Yogyakarta City Government maintains the Ngejaman monument without providing a narrative about the history of the monument's establishment in Malioboro. The government ignores historical literacy in tourism development in the Special Region of Yogyakarta, even when the importance of preserving the Ngejaman monument lies in its being a marker of the introduction of time as a regulator of modern human activity in Yogyakarta and a reminder that liberation has not necessarily meant freedom for all.